Post traumatic osteomyelitis of the femur or tibia: An evaluation of the clinical outcome, functional outcome, and quality of life - Zayzan, Khairul Rizal; Mohd Yusof, Nazri; Ab Rahman, Jamalludin (2016)
Aim: ” This study was conducted to investigate the clinical outcome, functional outcome, and quality of life of patients treated for post traumatic osteomyelitis (PTO) of femur and tibia in Hospital Tengku Ampuan Afzan, Kuantan, Malaysia from July 2007 to June 2014”